Towards the development of improved tests for negative symptoms of schizophrenia in a validated animal model - (:unkn) unknown (ELSEVIER SCIENCE BV, 2016)
Negative symptoms in schizophrenia remain an unmet clinical need. There is no licensed treatment specifically for this debilitating aspect of the disorder and effect sizes of new therapies are too small to make an impact on quality of life and function. Negative symptoms are multifactorial but often considered in terms of two domains, expressive deficit incorporating blunted affect and poverty of speech and avolition incorporating asociality and lack of drive. There is a clear need for improved understanding of the neurobiology of negative symptoms which can be enabled through the use of carefully validated animal models. While there are several tests for assessing sociability in animals, tests for blunted affect in schizophrenia are currently lacking. Two paradigms have recently been developed for assessing negative affect of relevance to depression in rats. Here we assess their utility for studying negative symptoms in schizophrenia using our well validated model for schizophrenia of sub-chronic (sc) treatment with Phencyclidine (PCP) in adult female rats. Results demonstrate that sc PCP treatment produces a significant negative affect bias in response to a high value reward in the optimistic and affective bias tests. Our results are not easily explained by the known cognitive deficits induced by sc PCP and support the hypothesis of a negative affective bias in this model. We suggest that further refinement of these two tests will provide a means to investigate the neurobiological basis of negative affect in schizophrenia, thus supporting the assessment of efficacy of new targets for this currently untreated symptom domain. (C) 2016 Elsevier B.V. All rights reserved.
Keywords: Schizophrenia; Negative symptoms; Animal model; NMDA receptor; PCP; Affective and cognitive bias; ANTERIOR CINGULATE CORTEX; COGNITIVE BIAS; SOCIAL WITHDRAWAL; RELEVANCE; STARLINGS; DEFICITS; TASK; PSYCHOPHARMACOLOGY; DYSFUNCTION; INDICATOR